Faulty detection on broadcasting equipment using thermal infrared imaging approach / Mohd Rizman Sultan Mohd - Sultan Mohd, Mohd Rizman (2019)
Thermal infrared is a non-invasive method for sensing temperature on specific time frame of its region of interest. It had been widely used as faulty detection on many applications including electrical transmission grid and electronics board. Broadcasting equipment operates 24-hours per day and yet sensing the faulty on fully functional equipment requires a non-invasive method. Broadcasting equipment separated into two; studio site and transmission site.